2020
DOI: 10.2174/1573407215666190405154406
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Synthesis and Pharmacological Activity of Coumarins and Their Analogs

Abstract: The biological, therapeutic and medicinal properties of coumarins and its analogs have prompted enormous research aimed at developing synthetic routes to these heterocycles. This review presents a systematic and comprehensive survey of the method of preparation, the chemical reactivity and biological properties associated with this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Some of these traditional uses are in accordance with the results from the abovementioned pharmacological studies with coumarin analogues-from the seed as well as other parts of the plant-showing a wide range of pharmacological activities [180][181][182]. This suggests that at least some of the traditional uses of D. odorata seed preparations are also attributable to antioxidant activities.…”
Section: Antioxidant Phenolic Compounds: Coumarins: Dipteryx Odorata ...supporting
confidence: 78%
See 1 more Smart Citation
“…Some of these traditional uses are in accordance with the results from the abovementioned pharmacological studies with coumarin analogues-from the seed as well as other parts of the plant-showing a wide range of pharmacological activities [180][181][182]. This suggests that at least some of the traditional uses of D. odorata seed preparations are also attributable to antioxidant activities.…”
Section: Antioxidant Phenolic Compounds: Coumarins: Dipteryx Odorata ...supporting
confidence: 78%
“…Besides anticoagulant activity, coumarins have been found to elicit a host of other pharmacological activities including antitumor, photochemotherapeutic, anti-HIV, antimicrobial, anti-inflammatory, triglyceride-lowering, central nervous systemstimulating, and menopausal distress-preventing effects [180][181][182]. These beneficial health effects are believed to be mainly related to their antioxidant activities, providing protection against oxidative stress by scavenging ROS such as superoxide, hypochlorous acid, and hydroxyl radicals [183].…”
Section: Antioxidant Phenolic Compounds: Coumarins: Dipteryx Odorata ...mentioning
confidence: 99%
“…[ 56,57 ] In view of all these facts and because of the continuation of our paintings on the synthesis of latest heterocyclic derivatives. [ 58‐65 ] The present review showed a broad view of the anti‐microbial properties expressed by compounds having a coumarin nucleus.…”
Section: Introductionmentioning
confidence: 93%
“…naturally in many plants and find wide use in medicine due to their diverse pharmacological activities [1,2]. They possess excellent photophysical properties such as high quantum yield, strong fluorescence, and high photostability, and therefore are used as dyes for biosensitization and biomarking [3].…”
Section: Coumarins Appearmentioning
confidence: 99%